Effectiveness of Impoverishment Punishment Implementation in Handling Corruption Crimes - Yasmirah Mandasari Saragih; Rahul Ardian Fikri; Nabilah Syaharani (International Journal of Law, Crime and Justice, 2024)
Corruption is a serious crime that has a wide impact on economic stability, public trust, and governance. Impoverishment punishment, as a form of alternative sanction, aims to provide a deterrent effect for perpetrators of corruption by confiscating assets obtained illegally. This study analyzes the effectiveness of the implementation of impoverishment punishment in the context of the legal system in Indonesia. The approach used is a normative and empirical study by evaluating existing regulations, case studies of the implementation of impoverishment punishment, and its impact on perpetrators and prevention of corruption in the future. The results of the study show that although impoverishment punishment has the potential to be an effective instrument, its implementation faces various challenges, including weak law enforcement, political resistance, and regulatory limitations. Therefore, legal reform and institutional strengthening are needed to ensure that this punishment can be implemented optimally in efforts to eradicate corruption.